PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MEMBANGUN PEMAHAMAN KONSEP - Herman Lusa; Irfan Supriatna (Jurnal Gentala Pendidikan Dasar, 2021)
This research is motivated by a lack of understanding in understanding mathematical concepts. This study aims to produce mathematics teaching materials using the Realistic Mathematics Education (RME) approach to build conceptual understanding. This research Research and Development (R&D) modifies the ADDIE model. In this study only up to the stage of development (Development). Validation is carried out by material experts, design experts, and linguists. There are two data analysis techniques in this study, namely qualitative descriptive statistical analysis of input, comments, and suggestions from expert validation sheets and peer-reviewed questionnaires, and descriptive statistical analysis of scores from expert validation results and peer responses. This research is expected to produce mathematics teaching materials based on Realistic Mathematics Education (RME) to build understanding of mathematical concepts in the form of ISBN modules.